Estudo da relação entre indicadores entomológicos para Aedes aegypti obtidos de MosquiTRAPs®, de armadilhas de oviposição e de coleta de adultos com aspiradores - Fávaro, Eliane Aparecida (2006)
The aims of this study were to identify the best place of residences to install MosquiTRAPs, traps capable of attracting and capturing Aedes aegypti females, to investigate the physiological state of captured females, to measure the entomological indicators for these mosquitoes and to evaluate their relationship with indicators from oviposition traps, adult collection, climatic data and dengue transmission. The research was performed in Mirassol SP, on two different occasions: Studies 1 and 2. For Study 1, an area of twenty blocks was selected, in which MosquiTRAPs were installed in five. Eight traps were set up in four houses of each block: four at indoor sites and four at shaded outdoor sites. These houses were visited during eight weeks. For Study 2, two areas were selected: Area 1 comprising 100 blocks and Area 4 comprising 30 blocks. One MosquiTRAP was installed in each block of Area 1 and four were installed in each block of Area 4. The traps were installed at outdoor sites at the residences and visited once a week. The collection of adult mosquitoes with Nasci aspirators was performed on a weekly basis in one house per block in Area 1 and four houses in Area 4. An oviposition trap was installed in one house of each block in both areas. These activities were performed over 23 weeks. Study 1 revealed that the MosquiTRAPs installed at outdoor sites captured 5 times more females than indoor traps. From the collected Aedes aegypti females, 87.3% were gravid and 86.7% had no blood in the middle intestine. Study 2 showed that only one MosquiTRAP per block is sufficient to quantify the number of females per house; the sensitivities of MosquiTRAPs and adult collections with aspirators to detect the presence of Aedes aegypti females were similar, yet inferior in relation to oviposition traps; the adjusted models for the positivity of MosquiTRAPs included climatic variables and excluded entomological indicators; the maximum values of mean numbers of females per house obtained by MosquiTRAPs and collections with aspirators were compatible with dengue transmission; disease transmission presented a self regressive behavior, although no relationships between the incidences of dengue and the mean number of females captured by MosquiTRAPs or by manual aspirators were identified.